Protective Effects of Hif2 Inhibitor PT-2385 on a Neurological Disorder Induced by Deficiency of Irp2 - Shen, Jiaqi; Xu, Li; Li, Yuxuan; Dong, Weichen; Cai, Jing; Liu, Yutong; Zhao, Hongting; Xu, Tianze; Holtz, Esther Meyron; Chang, Yanzhong; Qiao, Tong; Li, Kuanyu (Frontiers in Neuroscience, 2021)
Iron regulatory protein 2 (IRP2) deficiency in mice and humans causes microcytic anemia and neurodegeneration due to functional cellular iron depletion. Our previous in vitro data have demonstrated that Irp2 depletion upregulates hypoxia-inducible factor subunits Hif1α and Hif2α expression; inhibition of Hif2α rescues Irp2 ablation-induced mitochondrial dysfunction; and inhibition of Hif1α suppresses the overdose production of lactic acid derived from actively aerobic glycolysis. We wonder whether Hif1α and Hif2α are also elevated in vivo and play a similar role in neurological disorder of Irp2–/– mice. In this study, we confirmed the upregulation of Hif2α, not Hif1α, in tissues, particularly in the central nervous system including the mainly affected cerebellum and spinal cord of Irp2–/– mice. Consistent with this observation, inhibition of Hif2α by PT-2385, not Hif1α by PX-478, prevented neurodegenerative symptoms, which were proved by Purkinje cell arrangement from the shrunken and irregular to the full and regular array. PT-2385 treatment did not only modulate mitochondrial morphology and quality in vivo but also suppressed glycolysis. Consequently, the shift of energy metabolism from glycolysis to oxidative phosphorylation (OXPHOS) was reversed. Our results indicate that Irp2 depletion-induced Hif2α is, in vivo, in charge of the switch between OXPHOS and glycolysis, suggesting that, for the first time to our knowledge, Hif2α is a clinically potential target in the treatment of IRP2 deficiency-induced neurodegenerative syndrome.